Chlorophyll content in leaves of coriander as influenced by sowing dates, nitrogen and plant growth regulators (Indian Journal of Arid Horticulture, 2025)
Coriander (Coriandrum sativum L.) is one of the important leafy-green vegetable as well as seed spices crop grown in almost all states of India. Rajasthan occupies the first position both in production and acreage of coriander. The production of coriander in Rajasthan is 2.86 lakh tonnes from 2.41 lakh hectare land with the productivity of 1 190 kg per hectare (Anonymous, 2004). At present, India is export- ing only 5 per cent of the total produce. This is due to inability to withstand international quality standards of the produce. Therefore, there is an urgent need to increase the productivity and to upgrade quality so that it can with- stand competition in the international market (Singhal, 1999). The important limiting factors are poor package of prac- tices, untimely sowing, lack of adoption on judicious nutri- ents and also lack of knowledge on the use of plant growth regulators.
Keywords: Coriander; nutri- ents; adoption; Naphthalene acetic acid